La adaptación familiar y social de los menores adoptados internacionalmente. Seguimiento postadoptativo en la Comunidad de Madrid - Berástegui Pedro-Viejo, Ana (Miscelánea Comillas, 2012)
The aim of this study was obtaining information about family and social adaptation of inter country adoptees in Madrid Community using the postadoption follow up compulsory interviews. 276 protocols of follow up interviews were collected during a year, containing information about child and family characteristics, adoption process, child previous history, level of development, bonds and relationships with other people, child behavior, school adjustmentand family satisfaction level. Descriptive analysis shows a very positive outlook about inicial adaptation of this children although some difficulties are also highlighted. Results and their implications for postadoption follow up andsupport are discussed.